Enhanced activation of persulfate improves the selective oxidation of alcohols catalyzed by earth-abundant metal oxides embedded on porous N-doped carbon derived from chitosan. Issue 5 (2nd February 2023) - Oliveira, Rafael L.; Pisarek, Marcin; Ledwa, Karolina A.; Pasternak, Grzegorz; Kepinski, Leszek
Abstract : Metal clusters oxide were embedded in an N-doped carbon and used as catalysts for the activation of peroxydisulfate or peroxymonosulfate in the selective oxidation of benzyl alcohol. Quenching tests were done to investigate the reaction mechanism. Abstract : The selective oxidation of alcohols aiming at the formation of aldehydes and esters is an essential reaction for the fine chemical industry. However, the classical processes to obtain aldehydes present many limitations, such as waste generation, low selectivity, or high cost. Herein, we address the production and characterization of porous N-doped carbon derived from chitosan. This solid was used as the support for earth-abundant transition metal oxides such as Fe2 O3, CoO, NiO, or CuO nanoparticles. These materials were used as catalysts for the oxidation of primary alcohols by activating peroxydisulfate or peroxymonosulfate. Quenching tests were performed and a considerable contribution of a non-radical oxidation process was indicated.